2001
DOI: 10.1089/10507250152740920
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Crystal Structure of a Monoclonal Antibody That Binds to a Major Autoantigenic Epitope on Thyroid Peroxidase

Abstract: Thyroid peroxidase (TPO) catalyzes the production of thyroid hormones and is a major autoantigen in autoimmune thyroid disease (AITD). It is believed that the majority of TPO autoantibodies bind to an immunodominant region consisting of two overlapping domains. Precise location of these domains would help our understanding of the interaction between TPO and TPO autoantibodies. 4F5 is a mouse monoclonal antibody (IgG1, kappa) that reacts with high affinity (2.6 x 10(10) mol/L(-1)) with one of the major autoanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…8A) that interact with the indolic group of Trp258 of the LRD. The prominent presence of aromatic residues in the topography of the mAb combining site is consistent with aromatic residues being a usual feature of antibody binding sites (83,84).…”
Section: Fig 11supporting
confidence: 69%
“…8A) that interact with the indolic group of Trp258 of the LRD. The prominent presence of aromatic residues in the topography of the mAb combining site is consistent with aromatic residues being a usual feature of antibody binding sites (83,84).…”
Section: Fig 11supporting
confidence: 69%
“…Furthermore, we propose two possibilities to explain this phenomenon: either the MPO-like and CCP-like domains interact directly by interactions such as hydrogen bonds or salt links or the flexibility of the hinge region results in constant rearrangement among the three modules, and the binding of an aAb (like T13) on at least two domains "freezes" the structure into a stable conformation. If the latter alternative is true, this could explain why it is so difficult to obtain high resolution diffracting crystals of the TPO ectodomain (17,18). Co-crystallization of TPO with a specific Fab stabilizing the structure should solve this problem definitively.…”
Section: Discussionmentioning
confidence: 99%
“…Alignment studies and structural homologies have shown that TPO is formed by three distinct domains: a myeloperoxidase (MPO)-like, a complement control protein (CCP)-like, and an EGF-like domain, from the N-to the Cterminal extremities (13). Although the structure of each domain has been elucidated in part by three-dimensional modeling (13-16), the full three-dimensional structure of TPO remains unknown, even though low resolution crystals have been obtained (17,18). The flexibility observed for the hinge regions probably make difficult the exact positioning of each domain in relation to the others (15).…”
mentioning
confidence: 99%
“…Contacts between antibody and vascular endothelial growth factor (VEGF) are formed by van der Waals contact and improved hydrogen bonding . The site of Fab fragments of Abs against major autoantigenic epitope of thyroid peroxidase is rich in tyrosine residues . Thus, depending on the protein variable parts of monoclonal antibodies or Fab fragments recognizing various antigens can contain different AA residues forming with antigen electrostatic, hydrophobic, van der Waals contacts, and hydrogen bonding.…”
Section: Discussionmentioning
confidence: 99%